The recycling of electronic waste: regulations and corporate strategies in Brazil and in Europe. - Schneider, Alice Frantz (2016)
With the extreme growth of electronic waste worldwide and in Brazil, there is a huge need for enhancement of recycling processes for this sort of waste. Considering the extremely relevant topic, the main objective of this research is to study about regulations and corporate strategies towards electronic waste recycling in Brazil and to compare it with the European context. The specific objectives are: To analyse the general European scenario concerning sustainability and electronic waste, in order to compare it with the Brazilian scenario; to study the main regulations for the treatment of electronic waste in Europe and in Brazil; to identify the main actors involved in the recycling process of electronics in Brazil; to analyse how some of the main electronics\' manufacturers inform on their websites about actions towards recycling of electronics in Brazil and in Europe; and to study about how some of the main electronics\' manufacturers in Brazil are dealing with the recycling of electronics from both a strategic and operational point of view. With a qualitative nature, the research has different approaches in terms of methodology. Both the part of the European scenario and the part of institutional and legal aspects in Brazil are based on secondary data. The part of the case studies brings an analysis on the websites in Brazil and in the United Kingdom of some electronics\' manufacturers, results from the contact with their customer services in Brazil and a final part of interviews with two of these companies, one of these companies\' recycling partner and a recycling association of electronics. Among the main programmes from the European Commission identified towards a sustainable growth, there is The Europe 2020 Strategy and the 7th EAP. While the European Union has the WEEE and RoHS Directive in terms of legislation, Brazil relies on the National Solid Waste Policy (PNRS). Most of the companies analysed do not have a direct link for information about discard on their homepages in Brazil, while some do not have any information on the matter. By contacting the customer service support, some companies have provided divergent information from the websites. It has been possible to observe that many companies do not have proper actions towards the recycling of electronics in Brazil, in addition to not dealing with the residue in a strategic manner. The companies in the United Kingdom have, in general, better actions than the ones in Brazil, with most of the same companies having different actions according to the country. Among the main uncertainties identified in the recycling of electronics, there are: Different recycling technologies; unknown environmental impacts; different product design and composition; unknown reverse logistics costs; variable cost of recycling; rapidly changing nature of electronics; unpredictability about return of items concerning quantity, quality and timing; unknown destination of WEEE; different value of scrap materials; lack of common legislation; complexity of regulations; lack of environmental consciousness and lack of residues\' classification and regulations on the PNRS.